Hikmah Dan Nilai-Nilai Pendidikan Adanya Ayat-Ayat Muhkam Dan Mutasyabih Dalam Al-Qur’an - Dea Dwi Atika Yuditia; Dedi Masri; Muhamad Alfiyansah (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
The purpose of this study is to ascertain how the occurrence of muhkam and mutasyabih verses in the Qur'an affects knowledge and educational values. to use qualitative research techniques to examine the wisdom and educational benefits of the existence of muhkam and mutasyabih verses in the Qur'an. Using library research, which is a technique for gathering data by comprehending and assessing the theory in several literatures pertinent to this research, is the strategy used in this work. The findings of this study point to the wisdom and instructive value of the muhkam and mutasyabih verses in the Qur'an as well as the opinions of the scholars on these verses. Muslims must be more discerning in their interpretation of Allah's verses given the availability of muhkam and mutasyâbih verses in the Qur'an.